Perioperative management including dual cell salvage in a Jehovah's Witness patient undergoing major urological surgery. Issue 11 (19th November 2021) - Smith, Thomas G.; Anastasescu, Irina; Wight, James M.; Danaee, Anicee; Nair, Rajesh; O'Brien, Tim S.
Abstract: Complex surgery associated with major hemorrhage presents particular risks for Jehovah's Witnesses who do not accept transfusion of blood products. Intraoperative use of two cell saver machines simultaneously can maximize the yield of salvaged blood from both the operative field and from washed surgical swabs and can potentially be life‐saving. Abstract : Complex surgery associated with major hemorrhage presents particular risks for Jehovah's Witnesses who do not accept transfusion of blood products. Intraoperative use of two cell saver machines simultaneously can maximize the yield of salvaged blood from both the operative field and from washed surgical swabs and can potentially be life‐saving.